2020
DOI: 10.1371/journal.pone.0229856
|View full text |Cite
|
Sign up to set email alerts
|

Continuous intraocular pressure monitoring in patients with obstructive sleep apnea syndrome using a contact lens sensor

Abstract: PurposeTo analyse nocturnal intraocular pressure (IOP) fluctuations in patients with obstructive sleep apnea syndrome (OSAS) using a contact lens sensor (CLS) and to identify associations between the OSAS parameters determined by polysomnographic study (PSG) and IOP changes. MethodProspective, observational study. Twenty participants suspected of having OSAS were recruited. During PSG study, IOP was monitored using a CLS placed in the eye of the patient. The patients were classified according to the apnea-hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 64 publications
(80 reference statements)
2
14
0
Order By: Relevance
“…Interestingly, these fluctuations had no impact on the global IOP curves, which showed a similar pattern compared to those obtained in our study involving OSAS patients. As in a recent study by Carnero et al, 29 in which IOP was monitored using a CLS during a PSG study conducted with 20 OSAS patients without CPAP, we observed that patients with severe OSAS showed significant increases in nocturnal IOP values.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Interestingly, these fluctuations had no impact on the global IOP curves, which showed a similar pattern compared to those obtained in our study involving OSAS patients. As in a recent study by Carnero et al, 29 in which IOP was monitored using a CLS during a PSG study conducted with 20 OSAS patients without CPAP, we observed that patients with severe OSAS showed significant increases in nocturnal IOP values.…”
Section: Discussionsupporting
confidence: 85%
“…Carnero et al 29 showed that the length of the nocturnal IOP elevation was associated with respiratory parameters that were altered in patients with OSAS, meaning that patients who have better oxygen saturation show shorter nocturnal acrophase. Furthermore, a significant increase in IOP was observed as a response to short-term hypoxia, which returned to the baseline after hypoxia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patient cohort was split into severe and mild/moderate OSA. In contrast to Shinmei et al, patients with severe OSA showed a longer IOP elevation compared to patients with a mild/moderate disease ( p = 0.032/ p = 0.028) [ 15 ]. Fang et al investigated the differences in the IOP values during and after varying body positions in OSA and non-OSA patients.…”
Section: Introductionmentioning
confidence: 86%
“…These patients' medical histories were used to determine demographic data such as age and ethnicity as well as family history, arterial hypertension (high blood pressure) and diabetes mellitus histories. The findings in polysomnography determined the severity of OSA using the Apnoea/Hipopnea Index AHI (sum of apnoea and hypopnea events divided by total hours of sleep) to categorise it into one of three groups: mild (index 6-15), moderate (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and severe (>30). 16 Exclusion criteria include psychiatric or neurological disorders, optic neuropathy, anterior ischaemic optic neuropathy, heavy smoking (20 cigarettes per day), alcohol or psychoactive substance abuse, any condition affecting the VF (such as intracranial or ocular lesions), coexisting retinal disease, sequelae of trauma and/or eye inflammation, congenital ocular anatomical alterations, intraocular surgery (with the exception of cataract surgery), history of hypertensive crisis, history of prolonged steroid use, uveitis, bronchial asthma, interstitial lung diseases, heart disease, cirrhosis and chronic renal failure.…”
Section: Methodsmentioning
confidence: 99%